Analisa Protein dan Zat Pengawet (Nitrat dan Nitrit) Dalam Sosis Daging Sapi Siap Saji - Roslinda Rasyid; Yuli Anita; Krisyanella Krisyanella (STIFARM Padang, 2010)
A Qualitative analysis of nitrite and nitrate preservative and analysis of protein content in sausage fast food foundedin some markets in Padang has been done. The preservative in samples were extracted by mixing with water, and then identified by colour reaction. Analysis of preservative in samples was compared with standard preservative substance. From the identification, all samples contain preservative agent, nitrite and nitrate. Micro Kjehdahl method used to analysed protein in samples. The result showed that from each samples contained. Protein content 16.5% for samples A; 17.6% for samples B and 8.31% for samples C.